An Enhancement of Neutrosophic Exploratory Data Analysis Technique Using Hybrid Method - Taha Ayed, Mohammad; Nasir Husain, Qasim; Mahdi Alwan, Faris (Journal of Al-Qadisiyah for Computer Science and Mathematics, 2025)
In this research, a Hybrid method is made between the Hanning and Hamming methods so that this method depends on granting new weights to combine the two methods, which are merged through an algorithm that depends on its classification on the numerical method (BFGS) and was applied to three types of neutrosophic data on this method.